Productive Financing of Sharia Banks For MSMEs Development: A Systematic Literature Review - Trimulato, Trimulato; Rodoni, Ahmad; Amelia, Erika; Azis, Roikhan Muhammad (Jurnal Iqtisaduna, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economy, yet their access to productive financing from Islamic banks remains limited. Despite the growth of Islamic banking, the proportion of productive funding is still low compared to consumer financing, reducing its potential impact on the real sector. This study aims to analyze the contribution of productive funding by Islamic banks to MSME development and identify gaps in product innovation and regulatory challenges the sector faces. Using a systematic literature review (SLR) approach and bibliometric analysis with VOSviewer, the findings reveal that Sharia-based financing schemes such as mudharabah and musyarakah offer significant potential to enhance MSME resilience. However, limited financial literacy, product diversification, and stringent collateral requirements remain major barriers. This study recommends policies to improve Sharia financial literacy, develop flexible financing products, and reform regulations to support MSME access to productive financing. These findings underscore the strategic role of Islamic banks as catalysts for financial inclusion and drivers of sustainable economic growth.